A descriptive survey of the spatial and design preferences of selected coworking patrons in Makati City - Bautista, Ellen Joyce Angela P.
The study determined the spatial and design preferences of co-workers in a workspace and assessed how these elements affect the working conditions and efficiency of selected co-working patrons. Through purposive sampling, forty (40) coworkers, with thirty six (36) respondents and four (4) informants, were chosen to participate in the study. Respondents' professions were a mix of startups, freelancers, and business professionals. On the other hand, informants include an interior designer, a community manager and co-founders. The study employed a descriptive research design and included both qualitative and quantitative means of data gathering. The results have shown that the physical environment is one of the most important considerations in a co-working business. Spatial preferences pertaining to space allocation and configuration/layout include provision for both individual and collaborative spaces. The workspace must be flexible enough to accommodate all types of work and promote collaborative work, as well as maximize efficiency of cost for the business. Design preferences, on the other hand, pertain to lighting, treatment of color, and furniture selection. In accordance with the trend, warm white is considered prevalent in co-working spaces. However, it is important to provide both warm and cool white for different types of workers with different types of work that need to be done. Likewise, warm colors for the interiors were also prevalent because it encourages collaboration among workers. Moreover, furniture preferences were based on ergonomics that supports the well being of workers and mobility and multi functionality that facilitate flexibility in the workspace. Indeed, the work environment is highly influential to the performance and efficiency of the workers.